Professor coordenador pedagógico: dificuldades e possibilidades no seu cotidiano - Ribeiro, Margareth Mellão Garcia (2012)
This study was carried out to ponder on the Coordinating Teachers everyday actions within their school contexts. The main aim of our work was to analyze which are the difficulties and possibilities faced by them in their everyday life, investigating work conditions, taking into account their importance as managers of the curriculum within the context of two state public schools in São Paulo State. The methodology used here focused on the qualitative approach, whose procedures of data collection and analysis were biographical research and case study. The information was collected with four coordinating teachers who work in state public schools (at grade, junior and senior high school levels). To collect the data, one used two procedures: a questionnaire with closed questions and an interview with open questions. One managed to find out that such PCs presented features which may interfere in the conduction of the pedagogical work, taking on both a positive character in their function, admitting possibilities for work satisfaction and accomplishment in the management of their everyday work and a negative one, such as deviations from their function, bureaucratization, social rules, indiscipline. One believes that such a function is marked by changes occurred in educational reforms carried out in the 1970s, 1980s, 1990s, and 2000s, which, up to the present day, interfere in its significance.